Pengaruh Penerapan Model Pembelajaran Saintifik Berbasis Technological Pedagogical and Content Knowledge (TPACK) Pada Mata Pelajaran Geografi Terhadap Prestasi Belajar Siswa Di Kelas X SMAN 6 Seluma - Cici Andriani; Fevi Wira Citra; Edwar Edwar; Nurmintan Silaban (Universitas Prof. Dr. Hazairin, S.H, 2022)
The problem raised in this study is the low learning achievement of students in geography in class X social studies at Sman 6 Seluma. The purpose of this study was to determine the effect of applying scientific learning based on technological pedagogical and content knowledge (TPACK) in geography subjects to student achievement. This research was conducted in class X IPS SMAN 6 Seluma. The method used in this study is a quasi-experimental nonequivalent control group design. The population used in this study were 67 students of class X Social Sciences, the sample in this study there were 2 classes. Where class X IPS 1 as an experimental class using a scientific learning model based on TPACK and class X IPS 2 as a control class using scientific learning. Data collection techniques used pre-test and posh-test. The data analysis technique consists of validity test, reliability test, normality test, paired sample T-test, and independent sample T-test using the SPSS 16 application. ) = 0.000 < from 0.05. Therefore, it can be concluded that H0 is rejected and Ha is accepted. From the results of the study, it can be concluded that the Application of the Scientific Learning Model Based on Technological Pedagogical and Content Knowledge (TPACK) in Geography Subjects Has a Significant Effect on Increasing Student Achievement.